Fourth city : essays from the prison in America - Larson, Doran, 1957- (Michigan State University Press, 2014)
"At 2.26 million, incarcerated Americans not only outnumber the nation's fourth-largest city, they make up a national constituency bound by a shared condition. Fourth City: Essays from the Prison in America presents more than seventy essays from twenty-seven states, written by incarcerated Americans chronicling their experience inside. In essays as moving as they are eloquent, the authors speak out against a national prison complex that fails so badly at the task of rehabilitation that 60% of the 650,000 Americans released each year return to prison. These essays document the authors' efforts at self-help, the institutional resistance such efforts meet at nearly every turn, and the impact, in money and lives, that this resistance has on the public. Directly confronting the images of prisons and prisoners manufactured by popular media, so-called reality TV, and for-profit local and national news sources, Fourth City recognizes American prisoners as our primary, frontline witnesses to the dysfunction of the largest prison system on earth. Filled with deeply personal stories of coping, survival, resistance, and transformation, Fourth City should be read by every American who believes that law should achieve order in the cause of justice rather than at its cost."--EBL.